The Impacts of Armed Conflicts and Civilian Uprisings on Children's Health - Amir Khorram-Manesh (MDPI AG, 2022)
Besides the most common causes of death, children under 14 may suffer from the consequences of disasters and emergencies caused by natural and manmade risks and hazards. These incidents may be prevented by proper risk assessment and the prevention of unnecessary deaths by increasing the safety and well-being of children. An increasing number of manmade incidents are seen in international, non-international, and domestic conflicts when government forces use heavy and light weapons within countries with autocratic leadership. These deaths should be mitigated by holding perpetrators responsible for their deeds and respecting international humanitarian law, human rights, and children's rights.